2021
DOI: 10.2196/23612
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Ubiquitous Coaching With a Novel Combination of Mobile and Holographic Conversational Agents Targeting Adherence to Home Exercises: Four Design and Evaluation Studies

Abstract: Background Effective treatments for various conditions such as obesity, cardiac heart diseases, or low back pain require not only personal on-site coaching sessions by health care experts but also a significant amount of home exercises. However, nonadherence to home exercises is still a serious problem as it leads to increased costs due to prolonged treatments. Objective To improve adherence to home exercises, we propose, implement, and assess the novel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(88 citation statements)
references
References 99 publications
1
83
3
1
Order By: Relevance
“…Finally, we found that people who reported a better working alliance with the CA were more adherent to the intervention. This result is in line with studies about regular face-to-face interventions [24,25], digital therapy or treatment [26,27], and automated digital interventions [30,31,32,33,34]. Nonetheless, we did not find an effect of human cues on the reported working alliance with the CA.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Finally, we found that people who reported a better working alliance with the CA were more adherent to the intervention. This result is in line with studies about regular face-to-face interventions [24,25], digital therapy or treatment [26,27], and automated digital interventions [30,31,32,33,34]. Nonetheless, we did not find an effect of human cues on the reported working alliance with the CA.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, in studies that did find an improved working alliance with a CA either the interactions with the agent or the intervention itself were longer compared to those in our study [30,32]. In other studies, although a high working alliance was reported within shorter periods of time, the interactions with the CA followed after introduction by a human healthcare professional [33,34]. It is therefore unclear whether a TCA is less able to build a relationship with the user, or that it requires a longer time or introduction in a face-to-face introduction to do so.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…A total of 20 studies were included in this review, of which 1 study comprised 4 separate studies [ 29 ], resulting in 23 studies (representing 2231 participants) evaluated in this review. A summary and detailed description of the study characteristics are shown in Table 1 and Multimedia Appendix 3 [ 25 , 26 , 29 - 47 ] and Multimedia Appendix 4 [ 25 , 26 , 29 - 37 , 39 - 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Algorithms should update therapy plans and other training parameters (e.g., suggest transfer to another RehabGym device/exercise), and inform on overall rehabilitation progress. Additionally, exercise adherence and motivation could be increased by integrating a conversational agent (i.e., chatbot) that educates users on relevant topics (e.g., healthy lifestyle) and provides personalized motivational messages, as well as real-time exercise support, monitoring, and feedback as previously shown for physiotherapy patients and home exercise in a hands-free augmented reality environment ( Kowatsch et al, 2021 ). Building a strong “virtual” working alliance between a chatbot interface and a patient might prove a promising tool to improve the acceptance of the connected RehabGym and avoid mental/social distress caused by isolation.…”
Section: Going Beyond Covid-19: Moving Toward Minimally Supervized Robot-assisted Therapymentioning
confidence: 99%